(untitled) (Research, Society and Development, 2020)
This study seeks to outline and describe the epidemiological profile of notified and confirmed tuberculosis patients in the state of Piauí, from 2010 to 2015. This is a retrospective research, with a descriptive and exploratory approach, of a quantitative nature. In which secondary data were used, obtained from the Disease Information and Notification System. For tabulation and data analysis, the programs Tabwin 3.6 and Microsoft Office Excel 2013 were used. The results showed that in the period studied the disease had a higher and lower incidence in the years 2011 and 2015 respectively, being prevalent in people with incomplete elementary school. (42.59%), aged 40 to 59 years (35.04%), brown (69.31%), male (64.50%) and residing in the urban area (73.12%). Demonstrating that the risk of coming into contact with the bacillus and becoming ill from tuberculosis increases considerably in populations with an unfavorable socioeconomic level, compared to the population with higher purchasing power. Of the confirmed cases of tuberculosis, 5.23% and 5.57% of the sample had co-infection with AIDS and HIV respectively. It is concluded that this study has limitations for using secondary data, however it allowed to better understand the tuberculosis scenario in Piauí, as well as to observe during the analyzed years, that the number of tuberculosis cases in the state is still expressive, although there was a decrease in incidence in that period.